2022
DOI: 10.47176/mjiri.36.5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Status and Health System Screening of COVID 19 Hospitalized Patients in Isfahan, Iran

Abstract: Background: The first case of Covid-19 disease was identified in Iran on February 19, 2020, and spread rapidly throughout the country. The aim of this study was to investigate the characteristics of COVID-19 hospitalized patients in Isfahan province of Iran from February 29, 2020, to July 21, 2020, and evaluate the effect of health system screening on the final outcome patients. Methods: In this cross-sectional study, all patients with positive COVID-19 PCR test and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A recent study in Iran showed that about half of the people with a positive polymerase chain reaction (PCR) test for COVID-19 required hospitalization, and almost 5%, mainly with the underlying diseases of diabetes and hypertension, had to be rehospitalized. More than 50% of the hospitalized patients had not been screened by the health system, and the screening had no effect on the length of stay (LOS) and outcomes of the disease [ 6 ]. In addition, Baigi et al reported that older age, being male, history of comorbidities (especially cancer), and decreased consciousness at arrival were among the factors that could considerably increase the risk of death in hospitalized COVID-19 patients in Iran [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Iran showed that about half of the people with a positive polymerase chain reaction (PCR) test for COVID-19 required hospitalization, and almost 5%, mainly with the underlying diseases of diabetes and hypertension, had to be rehospitalized. More than 50% of the hospitalized patients had not been screened by the health system, and the screening had no effect on the length of stay (LOS) and outcomes of the disease [ 6 ]. In addition, Baigi et al reported that older age, being male, history of comorbidities (especially cancer), and decreased consciousness at arrival were among the factors that could considerably increase the risk of death in hospitalized COVID-19 patients in Iran [ 7 ].…”
Section: Introductionmentioning
confidence: 99%